Compounds of Group 14 Elements with an Element–Element (E = Si, Ge, Sn) Bond: Effect of the Nature of the Element Atom - Zaitsev K. V. Kirill; Lermontova E. Kh. Elmira; Churakov A. V. Churakov; Tafeenko V. A. Viktor; Tarasevich B. N. Boris; Poleshchuk O. Kh. Oleg Khemovich; Kharcheva A. V. Anastasia; Magdesieva T. V. Tatiana; Nikitin O. M. Oleg; Zaitseva G. S. Galina; Sergey S. S. Sergey (2015, 2015)
Title screen